2010
DOI: 10.1016/j.ejcts.2009.11.051
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of adoptive immunotherapy for recurrent non-small-cell lung cancer patients with autologous γδ T cells☆☆☆

Abstract: We suggest that gammadelta T-cell immunotherapy might be safe and feasible for patients with recurrent non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 16 publications
2
124
0
Order By: Relevance
“…Furthermore, six patients were alive at the end of the observation (240-850 days), demonstrating the potential of cd cell therapy for this condition. 45 Likewise, Nicol's team in Brisbane, Australia recently reported that when autologous transplants of In 111 -radiolabelled TCRVc9Vd2 1 cd T cells were tracked in 18 patients with advanced stages of various solid tumors, the cells trafficked predominantly to the lungs, liver and spleen in all patients but also to metastatic tumor sites in some patients. No dose-limiting toxicity was reported in this study, and three out of the 18 patients had clinical responses while continuing their previously ineffective chemotherapy.…”
Section: Rationale For Harnessing CD Cells In Cancer Immunotherapymentioning
confidence: 99%
“…Furthermore, six patients were alive at the end of the observation (240-850 days), demonstrating the potential of cd cell therapy for this condition. 45 Likewise, Nicol's team in Brisbane, Australia recently reported that when autologous transplants of In 111 -radiolabelled TCRVc9Vd2 1 cd T cells were tracked in 18 patients with advanced stages of various solid tumors, the cells trafficked predominantly to the lungs, liver and spleen in all patients but also to metastatic tumor sites in some patients. No dose-limiting toxicity was reported in this study, and three out of the 18 patients had clinical responses while continuing their previously ineffective chemotherapy.…”
Section: Rationale For Harnessing CD Cells In Cancer Immunotherapymentioning
confidence: 99%
“…PBMCs were used as the normal control target. Three thousand target cells labeled with 51 Cr sodium chromate (0.2 mCi/10 6 cells; Amersham Saclay, France) were cocultured in complete medium (RPMI) in 96-well U-bottomed plates for 4 hr with Vc9Vd2 T cells. The effector to target ratio (E:T) ranged from 1:1 to 60:1.…”
Section: Cytotoxicity Assays and Blocking Monoclonal Antibodiesmentioning
confidence: 99%
“…The expanded Vc9Vd2 T cells were tested for cytotoxicity against the EOC cell lines and autologous tumor cells from the primary tumor, carcinomatosis and ascites in a 4-hr standard 51 Cr release assay. PBMCs were used as the normal control target.…”
Section: Cytotoxicity Assays and Blocking Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…138 For adoptive transfer therapy, a single dose as large as 10 9 ex vivo expanded Vc9Vd2 cd-T cells has been confirmed to be safe by several independent investigations. [139][140][141] Encouragingly, these infused Vc9Vd2 cd-T cells exhibited satisfactory clinical benefit in an anti-tumor trial. 142 For in vivo applications, a single dose of (E)-4-hydroxy-3-methyl-but-2-enyl pyrophosphate plus 5 days of IL-2 treatment induced an 80-fold expansion of macaque peripheral blood Vc9Vd2 cd-T cells without detectable side effects.…”
Section: Current Strategies For Activating or Expanding Cd-t Cellsmentioning
confidence: 96%